Experimental Study on Electromagnetic Forming of High Strength Steel Sheets with Different Dimensions of Aluminum Driver Plate - Park, Hyeon Il; Kim, Daeyong; Lee, Jinwoo; Kim, Ji Hoon; Lee, Myoung-Gyu; Lee, Youngseon; Song, Jung Han (Technische Universität Dortmund, 2014)
Recently, the potential of the electromagnetic forming process has been introduced to form the shallow longitudinal reinforcement ribs in the lateral walls of roll formed parts, made of high strength steel sheets of 340MPa tensile stress grade [1]. However, it seems that the application may not be easy for high strength steel sheet because of its high tensile strength and low electric conductivity. In order to overcome this difficulty, aluminum driver plate could be considered to enhance the formability of high strength steel sheets in the electromagnetic forming process. In this paper, in order to investigate the effect of aluminum driver plate on forming height of high strength steel sheet in electromagnetic forming process, DP780 workpiece sheets were formed into a hemi elliptical protrusion shape with Al1050 driver plate of various thicknesses and sizes. Experiments were performed with a flat spiral coil actuator connected to an electromagnetic forming system. The results, the aluminum driver plate helps to increase the forming height of high strength steel sheets. In addition, the forming height of high strength steel sheet increases as the thickness and size of a driver plate increases.
Keywords: reinforcement rib; aluminum driver plate; electromagnetic forming; flat spiral coil; high strength steel sheet; 620; 670